The art of the Simon and Kirby studio - Simon, Joe 1913-2011; Kirby, Jack 1917-1994; Evanier, Mark 1952- (Abrams ComicArts, 2014)
"The names Joe Simon and Jack Kirby are synonymous with comic books, and their partnership ushered in the Golden Age of comics starting in the 1940s. Together they created memorable characters such as Captain America and the Sandman, and were the first to publish the genres of western, crime, horror, and romance in comic books. Over the course of three decades they wrote and illustrated several hundred comics, many of which are reproduced in this oversized volume organized by genre and covering all aspects of their amazing career. With commentary by Mark Evanier, the foremost authority on the work of Simon and Kirby, the book includes artwork photographed from the original art in Joe Simon's private archive and showcases the seminal work of Simon and Kirby and their artistry as it has never been seen before"...
Includes bibliographical references and index
Keywords: Simon, Joe -- Themes, motives; Kirby, Jack -- Themes, motives; ART / Popular Culture / bisacsh; COMICS & GRAPHIC NOVELS / General / bisacsh; Comic books, strips, etc -- United States -- History and criticism; ART / Popular Culture; COMICS & GRAPHIC NOVELS / General